PENERIMAAN GENERASI Z SURABAYA PADA KARAKTERISTIK GENERASI Z DALAM IKLAN GOJEK “SOLUSI MASALAH OVERTHINKING PILIH MAKANAN, ADA DI VIDEO INI!” - Mukhammad Shobri Kamil; Ahmad Zamzamy; Didiek Tranggono; Dyva Claretta (Ilmu Komunikasi, FISIP Universitas Pasundan, 2023)
This study focused to investigate how the Gen Z in Surabaya receives the representation of Gen Z characteristics that are visualized in the Gojek advertisement